The specificity of social metabolism of education in the context of globalization - Крохмаль, Н. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article analyzes the specifics of intersystem exchange of education as a social institution and a social system with other systems ofsociety. It considers social metabolism of education with science and economy of the globalized world, knowledge management isviewed as a result and the ultimate goal of exchange in the modern society.